Sistem Pemetaan dan Pelaporan Rumah Tidak Layak Huni berbasis Web (Studi Kasus : Dinas Perkim Kabupaten Magetan) - Riyanda Satriyo Wicaksono; Adam Hendra Brata; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
At this time, the government is very aggressive in implementing programmes to reduce poverty in this country, including the Family Hope Programme (PKH), Healthy Indonesia Card (KIS), and several more. One of the programmes currently running is the Self-Help Housing Stimulant Assistance (BSPS) or commonly referred to as house renovation. BSPS itself is government assistance for Low-Income Communities (MBR) to encourage and increase self-help in improving the quality of houses and new construction of houses, along with infrastructure, facilities, and public utilities (Regulation of the Minister of PUPR Number 07/PRT/M/2018). However, the current implementation of the assistance programme still uses conventional methods in collecting data related to potential beneficiaries, one of which is data on uninhabitable houses or we call them RTLH. The lack of a tool to help make reports if there are uninhabitable houses in the vicinity is also one of the limitations in this conventional method. Therefore here a solution to the problem is made, the solution is a website-based system that has features to help RTLH reporting, help handle the report, and help collect RTLH data. The stages in this research are literature study, requirements engineering, design, implementation, testing, and conclusions. In the SDLC requirements engineering stage used is the waterfall model, in the requirements engineering also obtained 24 functional requirements, 1 non-functional requirement, and 4 actors. System testing uses unit testing and validation testing. The results of system testing show that the system runs properly in accordance with the design.